Temperature and illumination dependence of silicon heterojunction solar cells with a wide range of wafer resistivities. (22nd December 2022) - Le, Anh Huy Tuan; Srinivasa, Apoorva; Bowden, Stuart G.; Hameiri, Ziv; Augusto, André
Abstract: Recently, the significant improvements in the surface and contact passivation of silicon (Si) solar cells as well as their bulk quality have shifted their operating point to higher injections. Hence, they are less dependent on wafer doping. This shift opens an opportunity of using high‐resistivity wafers for practical photovoltaic applications, introducing a promising approach to push the cell efficiency towards the intrinsic limit and to improve the module reliability by increasing the cell breakdown voltage. Therefore, insights into the performance of Si solar cells using high‐resistivity wafers at various operating temperatures are of significant interest. In this study, we investigate the temperature‐ and illumination‐dependent performance of Si heterojunction (SHJ) solar cells using a wide range of wafer resistivities (between 3 and 1000 Ω⋅cm). Although a reduction in the passivation quality of the passivating contacts is observed at elevated temperature, the impact on the temperature coefficient of the open‐circuit voltage (TC V oc )—the dominant contributor to the temperature coefficient (TC) of the cell efficiency—is very limited. Their TC V oc are still dominated by the temperature dependence of the effective intrinsic carrier concentration. Furthermore, we also find that the investigated cells are more sensitive to temperature variation at lower illumination intensities. It is noteworthy that the efficiency of the cells fabricated using high‐resistivity wafers is comparable to that of the reference cells at any given temperature, highlighting the potential of using high‐resistivity wafers for solar cells. Abstract : We investigated the temperature‐ and illumination‐dependent performance of silicon heterojunction (SHJ) solar cells using a wide range of wafer resistivities (3–1000 Ω⋅cm). The efficiency of the cells fabricated using high‐resistivity wafers is comparable to that of the reference cells at any given temperature. The findings demonstrate that there is no limitation in using high‐resistivity wafers for SHJ solar cells under field operating conditions.